Chromosomal 1q21 abnormalities in multiple myeloma: a review of translational, clinical research, and therapeutic strategies. Issue 12 (2nd December 2021) - Bisht, Kamlesh; Walker, Brian; Kumar, Shaji K.; Spicka, Ivan; Moreau, Philippe; Martin, Tom; Costa, Luciano J.; Richter, Joshua; Fukao, Taro; Macé, Sandrine; van de Velde, Helgi
ABSTRACT: Introduction: Multiple myeloma (MM) remains an incurable disease with a median overall survival of approximately 5 years. Gain or amplification of 1q21 (1q21+) occurs in around 40% of patients with MM and generally portends a poor prognosis. Patients with MM who harbor 1q21+ are at increased risk of drug resistance, disease progression, and death. New pharmacotherapies with novel modes of action are required to overcome the negative prognostic impact of 1q21+. Areas covered: This review discusses the detection, biology, prognosis, and therapeutic targeting of 1q21+ in newly diagnosed and relapsed MM. Patients with MM and 1q21+ tend to present with higher tumor burden, greater end-organ damage, and more co-occurring high-risk cytogenetic abnormalities than patients without 1q21+. The chromosomal rearrangements associated with 1q21+ result in dysregulation of genes involved in oncogenesis. Identification and characterization of the 1q21+ molecular targets are needed to inform on prognosis and treatment strategy. Clinical trial data are emerging that addition of isatuximab to combination therapies may improve outcomes in patients with 1q21+ MM. Expert opinion: In the next 5 years, the results of ongoing research and trials are likely to focus on the therapeutic impact and treatment decisions associated with 1q21+ in MM.